ZAKAT SOLUSI PEMBERDAYAAN MASYARAKAT - Muhammad Anis (El-Iqthisadi, 2020)
AbstractZakat is an obligation for those who have the ability called Muzakki which aims to help others and for those who don’t have the ability to be called Mustahik, including the poor, amil, converts, people who owe, people who demand knowledge, and people who struggle in the way of Allah Swt. Besides that, zakat can also be a tool for empowering Muslims. The Muzakki, Amil and Zakat Collecting Institutions must be at the forefront in the process of empowering umad, according to Minister of Religion Regulation No. 52 of 2014, Zakat is a treasure that must be issued by a Muslim or a business entity owned by Muslims to be given to those entitled to receive it in accordance with Islamic law. According to QS. At-Taubah verse 60, that Allah gave the provisions there are eight groups of people who receive Zakat. In general, Zakat is divided into two types of Zakat Fitrah and Zakat Harta (Mal). Zakat Fitrah must be issued in the holy month of Ramadan for every soul both men and women with Islamic religious requirements, Living on the Month of Ramadan, Having food or basic needs for the night of Eid al-Fitr. Zakat Harta (Mal) is zakat which is issued if the nizab has been fulfilled and is not in conflict with religious law. Keywords: Community Empowerment, Solutions, Zakat.AbstrakZakat merupakan Kewajiban bagi yang punya kemampuan dinamakan Muzakki yang bertujuan untuk membantu orang lain dan bagi tidak punya kemampuan dinamakan Mustahik, diantaranya adalah Fakir, Miskin, Amil, Muallaf, Orang Yang berutang, Orang yang Menuntut Ilmu, dan Orang yang berjuang dijalan Allah Swt. Disamping itu zakat juga dapat menjadi alat pemberdayaan ummad. Para Muzakki, Amil dan Lembaga Pengumpul Zakat (UPZ) harus berada pada garda terdepan dalam dalam proses pemberdayaan umad, menurut Peraturan Menteri Agama  no 52 Tahun 2014, Zakat adalah Harta yang wajib dikeluarkan  oleh seorang muslim atau badan usaha yang dimiliki oleh orang islam untuk diberikan kepada yang berhak menerimanya sesuai dengan syariat Islam. Menurut QS. At-Taubah ayat 60, bahwa Allah memberikan ketentuan ada delapan golongan orang yang menerima Zakat. Secara umum Zakat terbagi menjadi dua jenis yaitu Zakat Fitrah dan Zakat Harta (Mal). Zakat Fitrah wajib dikeluarkan pada bulan suci ramadhan atas setiap jiwa baik laki laki maupun perempuan dengan syarat beragama Islam, Hidup pada Bulan Ramadhan, Memiliki kebutuhan makanan atau kebutuhan pokok  untuk pada malam hari raya idul fitri. Zakat Harta (Mal) adalah zakat yang dikeluarkan jika nizabnya sudah terpenuhi dan tidak bertentangan dengan syariat agama.Kata Kunci : Pemberdayaan Masyarakat, Solusi, Zakat.